Practical Synthesis of Fludarabine and Nelarabine - Shen, Chunyang; Liu, Jiang; Ouyang, Wenliang; Ding, Haixin; Bai, Jiang; Xiao, Qiang (Synthesis, 2020)
A new practical synthesis strategy has been developed to access the β-d-arabinofuranosyl purine nucleosides fludarabine and nelarabine. In our approach, an ortho-alkyne benzoyl ester is transiently introduced as a neighbouring-participation group in Vorbrüggen glycosylation to afford the corresponding β-nucleoside exclusively. The latter was further removed efficiently by using freshly prepared Ph3PAuOTFA to give the corresponding 2′-OH nucleosides without transesterification. After reversion of the configuration of 2′-OH and deprotection, fludarabine and nelarabine were obtained in high yield and purity.
Keywords: fludarabine; nelarabine; gold(I) catalysis; total synthesis; ortho-alkyne benzoyl ester; β-d-arabinofuranosyl purine nucleosides; Vorbrüggen glycosylation